2019
DOI: 10.1002/slct.201900363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Graphene Oxide/Metal‐Organic Frameworks Composite Materials for Removal of Congo Red from Wastewater

Abstract: In‐based metal‐organic frameworks (In–MOFs) and graphene oxide (GO)/ In–MOFs composite materials were obtained by trimesic acid (or 2‐aminoterephthalic acid), GO, and Indium chloride tetrahydrate milled microwave‐assisted ball milling. Scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and X‐ray diffraction (XRD) were applied to characterize the structure and thermostability of the synthesized composite materials. In addition, In–MOFs and GO/ In–MOFs were used for removal of organic dyes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…In the Langmuir model, the maximum adsorption occurs when the absorbent surface is completely covered by the target species and the solid surface is homogeneous. Under such conditions, monolayer adsorption takes place [57,58]. The Freundlich model considers the adsorption phenomenon as a multi-layered and heterogeneous phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In the Langmuir model, the maximum adsorption occurs when the absorbent surface is completely covered by the target species and the solid surface is homogeneous. Under such conditions, monolayer adsorption takes place [57,58]. The Freundlich model considers the adsorption phenomenon as a multi-layered and heterogeneous phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Meili et al, 2019 found that LDH-biochar composites which synthesized via co-precipitation to remove dyes with adsorption capacity reaching 406.47 mg/g. Wei et al, 2019 research using ln-MOFs LDH which was composited with graphite could remove CR with a maximum capacity of 70.1 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, long-term ball milling may also cause the MOF structure to collapse, lose its periodic structure, and become amorphous [84,85], which is difficult to achieve in a solution phase reaction. The ball milling method can also make it more convenient to combine MOFs and other materials to form binary or even multiple composite materials [18,[86][87][88][89][90][91][92][93], such as GO/MOFs composites [94][95][96][97][98][99] Cu-BTC with truncated octahedral shape, and showed significantly reduction of reaction time and effectively improvement of yield [78].…”
Section: Comparison Of Ball-milling and Solution Methodsmentioning
confidence: 99%